1998
DOI: 10.1159/000007151
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cefepime, Cefixime and Ceftibuten on Murine Gut Colonization by <i>Candida albicans</i>

Abstract: Crl:CD1(ICR) BR mice were fed chow containing Candida albicans or regular chow. Both groups were subsequently given either antibiotics or normal saline. Stool cultures were performed before, at the end of treatment and 1 week after treatment, to determine the effect on the stool yeast concentration. Candida-colonized mice treated with cefepime, cefixime or ceftibuten had higher (however not significantly) counts of the yeast in their stools than control Candida-fed mice treated with saline. A group of Candida-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…This model has been shown to mimic human conditions and has been proven useful in predicting the effects of antimicrobial agents on human GI colonization by Candida [10].…”
Section: Discussionmentioning
confidence: 99%
“…This model has been shown to mimic human conditions and has been proven useful in predicting the effects of antimicrobial agents on human GI colonization by Candida [10].…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary analyses in our lab- In summary, we found that antibiotics that inhibited intestinal anaerobes based on DGGE analysis (piperacillin-tazobactam, ceftriaxone, metronidazole, and clindamycin) promoted persistent high-density colonization with C. glabrata. Antibiotics that inhibited facultative gram-negative bacilli but not anaerobes (levofloxacin, cefepime, and aztreonam) did not promote C. glabrata colonization; other investigators have demonstrated that such agents either do not promote intestinal colonization with C. albicans or do so only to a modest degree (4,5,7,8,10,11). Antibiotic-associated overgrowth of Candida species in the gastrointestinal tract may have important clinical implications.…”
mentioning
confidence: 98%
“…Antibiotics play a crucial role in the pathogenesis of Candida infections by inhibiting competing indigenous microflora, thereby facilitating acquisition and overgrowth of Candida species in the gastrointestinal tract and at other sites (1). Several studies suggest that antibiotics that inhibit obligate anaerobes in the intestinal tract may be more likely to promote overgrowth of C. albicans than those that do not (1,4,5,7,(8)(9)(10)(11), but little data regarding the effect of antibiotics on colonization with other Candida species are available. We used a mouse model to test the hypothesis that antibiotics with potent activity against intestinal anaerobes (piperacillin-tazobactam, metronidazole, ceftriaxone, and clindamycin) promote overgrowth of Candida glabrata, whereas agents with minimal activity against anaerobes (cefepime, levofloxacin, and aztreonam) do not.…”
mentioning
confidence: 99%
“…Modern cytotoxic and immunosuppressive therapies are limited by the inadequate availability of effective, non‐toxic antifungal antibiotics and the lack of effective immunotherapies has made Candida one of the five most often isolated microbes from blood cultures 7 . In the hope of minimizing further interference with the gut ecosystem secondary to the use of chemically synthesized antifungal molecules 2,3,13,36 a number of different approaches, such as the use of phytochemicals are under investigation 37,38 . In the present study we used a natural phytotherapeutic agent based on anethole/polygodial, which we have previously shown to significantly inhibit Candida adhesiveness to duodenal mucosa as well as limiting its gut translocation 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The extensive use of parenteral nutrition 1 and antibiotics, 2,3 as well as some therapeutic regimens or ongoing disease deranging the immune system, 4–6 have been suggested to significantly elicit fungal infections. Indeed, the incidence of candidiasis has been steadily increasing over the past decade 7,8 .…”
Section: Introductionmentioning
confidence: 99%